Enhancing Intercultural Communication through English Literacy in an institutional context: The case of a Second Chance School in a State penitentiary - (:unkn) unknown (My University, 2022)
Teaching English as a Foreign Language in a restricted educational context as that of a State penitentiary is a multifaceted endeavor within the framework of Adult Education. There are several restrictions for the Educators teaching and the trainees attending any subject within the specific context of the Second Chance Schools. The aim of this study is not only to highlight these limitations, but mainly to investigate the potentials the trainees have to develop both Intercultural Communication and Awareness through the English lessons taught. In order to achieve the aforementioned aims a research was conducted using two research tools, a ten-item questionnaire to look into the degree of ICC and ICA that trainees can build up and semi-structured interviews to point out the limitations that both educators and trainees come up with during the educational process in the SCS in Corfu’s (Greece) State Penitentiary. The research findings confirmed the researcher’s hypothesis that the English language lessons can have a positive contribution to incarcerated trainees developing ICC and ICA in class. Furthermore, quite interesting were the findings about the limitations and difficulties the Educators and trainees have, as these were related not only with practical issues (limited financial support, resources etc.) but also with educational matters as that of the limited communication between Educators and their students. The study concludes with suggestions for further research on the specific topic.
Keywords: Εκπαίδευση Ενηλίκων, κρατούμενοι εκπαιδευόμενοι, Διαπολιτισμική Εκπαίδευση, Διαπολιτισμική Επίγνωση, Σχολεία Δεύτερης Ευκαιρίας; Adult Education, incarcerated trainees, Intercultural Communication, Intercultural Awareness, Second Chance Schools